Dinamika Transfigurasi Tata Kelola Global: Posisi Indonesia dalam Restrukturisasi Lanskap Geopolitik Melalui Ekspansi BRICS - Milia, Jana; Attamimi, Salsabilah (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
This study aims to analyze Indonesia's strategic position in the expansion of BRICS (Brazil, Russia, India, China, and South Africa), which marks a shift in the global geopolitical landscape. Adopting the principle of multipolarity, BRICS seeks to establish a more inclusive and equitable global governance system. As a developing country with significant economic strength and a commitment to global cooperation, Indonesia has substantial opportunities to contribute to this transformation. This research will explore how BRICS expansion impacts Indonesia's role and position in restructuring the global geopolitical landscape. The concepts and perspectives employed include the Regional Security Complex and Polarity in International Relations. The research uses a qualitative descriptive-explanatory method, with data collected through literature review. The findings indicate that Indonesia can play a crucial role in promoting global governance reform, strengthening South-South cooperation, and balancing geopolitical dynamics. However, challenges such as the diversity of member interests, barriers to economic integration, and geopolitical tensions must be addressed. BRICS provides a strategic platform for Indonesia to expand its international influence while supporting sustainable development through initiatives like the New Development Bank. Thus, Indonesia is not merely a beneficiary but also a key actor in shaping the future of global governance. Keywords: BRICS, Indonesia, Global Order, Geopolitics, Economy, Multipolarity, South-South Cooperation